Wymagania w zakresie stażów prokuratorskich w świetle art.14a ustawy z dnia 20 czerwca 1985 r. o prokuraturze Dz.U. z 2008 r. Nr 7, poz. 39 z późn. zm. - Myrna, Bogdan (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The article focuses on the subject matter set out in Article 14a of the Prosecution Service Act. The provision defines a requirement in the form of a specified traineeship for appointment to a prosecutor position. The requirement concerns a specific length of traineeship for particular prosecutor positions or equivalent judge positions or a specific length of practice as an attorney, solicitor or notary public. Additionally, the author discusses possibilities for particular prosecutor positions to be held by persons with appropriate academic degrees in law.
Keywords: prosecution service; appointment to position; traineeship; academic degree